Neutron diffraction and gravimetric study of the manganese nitriding reaction under ammonia decomposition conditions - Wood, T; Makepeace, J; David, W (American Chemical Society, 2018)
Manganese and its nitrides have recently been shown to co-catalyse the ammonia decomposition reaction. The nitriding reaction of manganese under ammonia decomposition conditions is studied in situ simultaneously by thermogravimetric analysis and neutron diffraction. Combining these complementary measurements has yielded information on the rate of manganese nitriding as well as the elucidation of a gamut of different manganese nitride phases. The neutron diffraction background was shown to be related to the extent of the ammonia decomposition and therefore the gas composition. From this and the sample mass, implications about the rate-limiting steps for nitriding by ammonia and nitriding by nitrogen are discussed.